VD_FINDINFO Jug / 2014 / 103 vom 2. September 2013 - VD Tribunal cantonal (2013)
CONSTATATION DES FAITS, VIOLENCE CONTRE LES AUTORITÉS, LÉGITIME DÉFENSE, EXCÈS | 14 CP, 15 CP, 16 CP, 398 al. 3 let. b CPP (CH)